La metáfora biológica en la obra de Manuel González Prada - Fernández-Cozman, Camilo Rubén (Studia Romanica Posnaniensia, 2020)
Manuel González Prada is one of the most important Latin American authors. He used the biological metaphor to criticize Peruvian society in the late nineteenth century. The metaphor of disease, animal and plant are three kinds of analog procedures that González Prada uses according to a naturalistic vision, heiress of Spencer's evolutionism. González Prada questions the imitation and lack of stylistic precision of writers in the nineteenth century, as well as conceiving that Peru is a sick organism